-3x-4=-9-4x

Simple and best practice solution for -3x-4=-9-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-4=-9-4x equation:


Simplifying
-3x + -4 = -9 + -4x

Reorder the terms:
-4 + -3x = -9 + -4x

Solving
-4 + -3x = -9 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-4 + -3x + 4x = -9 + -4x + 4x

Combine like terms: -3x + 4x = 1x
-4 + 1x = -9 + -4x + 4x

Combine like terms: -4x + 4x = 0
-4 + 1x = -9 + 0
-4 + 1x = -9

Add '4' to each side of the equation.
-4 + 4 + 1x = -9 + 4

Combine like terms: -4 + 4 = 0
0 + 1x = -9 + 4
1x = -9 + 4

Combine like terms: -9 + 4 = -5
1x = -5

Divide each side by '1'.
x = -5

Simplifying
x = -5

See similar equations:

| 23.1=6.6x | | 17-2(x+3)=9 | | -6x-46=-11x+74 | | (1+2x)/7+(5-x)/3=37/21 | | .11k+1.5=2.4 | | 19.79+0.8-12.3c=-19.71-14.9c | | 5x-6(x+3)=15 | | 3x-7+2x+4-7x= | | -79+x=54+8x | | a/7+5/7+2/7 | | 8b-0.5=9b | | -190-2x=-10x+50 | | y-12=-3 | | Y+2=5y-6 | | 8-9(k-3)=14k-11 | | b/5=19 | | x^2+14x=-20 | | 5x^2=2x-7 | | 4x-5(x+3)=16 | | 4+x=-13 | | 5x+21=2x+15 | | -2.86-17.1t=5.24-15.3t | | 5x+6=x+22 | | 1/3(2x+4)+5=-2/3(x+1) | | 6.25x+12=30.75 | | 2/3(4x-10) | | 9v-6=5v+18 | | (6x+15)/4=-15x-25+(5/4) | | 8-9(3-k)=14k-11 | | 10[3p+4]-1=49 | | 1/3(2x-1)+1/4(1/2-3x)=-2 | | 5x+21=2x+25 |

Equations solver categories